Plant Invasions in Protected Areas Patterns, Problems and Challenges - Foxcroft, Llewellyn C.; Py¿Łek, Petr.; Richardson, David M.; Genovesi, Piero. (Invading Nature - Springer Series in Invasion Ecology, 2013)
This book is the first comprehensive global review of all aspects of alien plant invasions in protected areas. It provides insights into advances in invasion ecology emanating from work in protected areas, and the link to locally relevant management support for protected areas. The book provides in-depth case studies, illuminating interesting and insightful knowledge that can be shared across the global protected area network. The book includes the collective understanding of 80 ecologists and managers to extract as much information as possible that will support the long-term management of protected areas, and the biodiversity and associated ecosystem services they maintain. ỚSThis outstanding volume draws together pretty much all that can be said on this topic, ranging from the science, through policy, to practical actionỚ<U+00fd>. Dr. Simon N. Stuart, IUCN Species Survival Commission, UK. "This important and timely volume addresses two of the most serious problems affecting biodiversity conservation today: assessing the extent to which protected areas are impacted by biological invasions and the complex problems of managing these impacts. Written by leading specialists, it provides a comprehensive overview of the issues and gives detailed examples drawn from protected areas across the world". Professor Vernon H. Heywood, School of Biological Sciences, University of Reading, UK℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ ℗ .